2009
DOI: 10.3917/psyt.151.0115
|View full text |Cite
|
Sign up to set email alerts
|

La quête de risques extrêmes

Abstract: Distribution électronique Cairn.info pour De Boeck Supérieur. © De Boeck Supérieur. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The authors reported that the BASE jumpers showed significantly more clinical pathological personality features from Cluster B of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision classification compared with control participants. Finally, Ranieri (2009) has speculated that extreme sports athletes evidence personality deficits and a pathological addiction to extreme risk seeking that contributes to their involvement in these activities.…”
mentioning
confidence: 99%
“…The authors reported that the BASE jumpers showed significantly more clinical pathological personality features from Cluster B of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision classification compared with control participants. Finally, Ranieri (2009) has speculated that extreme sports athletes evidence personality deficits and a pathological addiction to extreme risk seeking that contributes to their involvement in these activities.…”
mentioning
confidence: 99%
“…The ‘narrow escape’ can be defined as a trauma which has been avoided. In a previous paper (Ranieri, 2009), I proposed a comparison between emotions caused by risk seeking and those which follow a trauma, more exactly due to Post‐Traumatic Stress Disorder (PTSD). The emotions described by risk takers seem to be mirror images of those experienced by victims of a psychological trauma.…”
Section: Risk Seeking As a Pathological Addictionmentioning
confidence: 99%